Любовь к шестерым - Бакунина Екатерина Васильевна (Фавориты любви, 2001)
Экземпляры: ФО-3 (201410) / Инвентарный номер: 50282 / Цена: 40.00 / Сис.шифр: Р2 / Авт.знак: Б 19 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6